PENGEMBANGAN MASYARAKAT BERBASIS KEWIRAUSAHAAN UNTUK MENINGKATKAN PARIWISATA DAN BUDAYA DI KAMPUNG WISATA SUKADIRI KOTA SERANG - Sukarta Atmaja; dedi Juniansha (Jurnal Manajemen dan Bisnis, 2019)
Abstract: Entrepreneurship-based community development to improve tourism and culture in Sukadiri tourism village Serang is one form of activity in the economic field by empowering the tourism village community. Sukadiri Tourism Village has a special agenda in the field of culture which is one of the efforts in preserving the culture in the village including wayang suket, ketoprak, art lesung and jathilan. Along with the increase of visitors both domestic and foreign tourists so that there is a need for entrepreneurship development in Sukadiri Tourism Village so that later it can improve the standard of living in the economic field, especially for the people in Sukadiri Tourism Village. In making tourism village development successful, strategic efforts that need to be developed include: human resource development, profitable partnerships, village government activities, tourism promotion activities, village festivals, village community organization development, collaboration with universities. Entrepreneurship development in a village tourism certainly requires the cooperation and infrastructure that supports tourism activities in Sukadiri village including eco- lodge, eco-recreation, eco-education, eco-research, eco-energy, eco-development, and eco-promotion. Some forms of entrepreneurship that can be developed in Sukadiri tourism villages include being a tour guide, providing culinary services, providing accommodation, making tour packages, providing transportation to and from Sukadiri tourism villages, providing typical village souvenirs.